VALIDITAS PENAFSIRAN DALAM TAFSÃR BI AL-MAâTSÃR - Hudaya, Hairul (Fakultas Ushuluddin dan Humaniora IAIN Antasari, 2010)
There are three methods of interpretation used by commentators to interpret the Qurâanic verses, by riwayah, knownas tafsÃ®r bi al-maâtsÃ»r, by logic known as tafsÃ®r bi al-raâyi and by al-isyÃ¢ri. From three methods of interpretation,according to Ibn Taymiyyah, tafsÃ®r bi al-maâtsÃ»r is the best method and valid. It is based on the belief that knows themeaning of the verse is Allah, the Prophet, and his companions. In fact, the commentary by al-maâtsÃ»r, not the wholeverse is interpreted by the Prophet, or friends but the majority carried out by commentators with ijtihadnya in placingthe Qurâan, Hadith and friends opinion when interpreting a verse. Thus, differences in interpretation among commentatorsbi al-maâtsÃ»r can not be avoided. In case of Abrahamâs son who was sacrificed, for example, between al-Thabari, Ibn KatsÃ®r and Ibn âAthiyyah had different opinions and attitudes of understanding of the verses. Whiletheir interpretation is called tafsÃ®r bi al-maâtsÃ»r. Their different opinions indicate that al-tafsÃ®r bi al-maâtsÃ»r also needa review of the validity, especially related to commentatorâs thought in placing the explanation of Qurâan itself,Hadith and opinion in interpreting the Qurâanic verses